If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -5v = 3 Reorder the terms: -5v + x = 3 Solving -5v + x = 3 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-1x' to each side of the equation. -5v + x + -1x = 3 + -1x Combine like terms: x + -1x = 0 -5v + 0 = 3 + -1x -5v = 3 + -1x Divide each side by '-5'. v = -0.6 + 0.2x Simplifying v = -0.6 + 0.2x
| 101-3x=33x+21 | | 4b+b=20 | | 8-8x=53-29x | | 2(2x+7)+9=3+2x | | -3k+7k=-8 | | 5t-8=3t | | 6x-69=4x-13 | | 4(d+2)=30 | | n-7+6n=-21 | | 5t^2=6t | | 2*(3x+5)-5*(6x-6)=8*(10x-8) | | 6x+34=15x-65 | | 4x^2+4x=8 | | 5x^3+2x^2+20x+8=0 | | 45x^2+3x=0 | | 80-2x=25x+20 | | 3n^2-5n-8=0 | | 5x^2-30x+20=0 | | 2n-3=17+n | | 3-3m-5=-5 | | 6-9x=130-37x | | 2v+6-7v=11 | | 4m=52 | | -3r-5r=8 | | y=(-2xp)-4 | | 6+2n=4n+8 | | y=(-2x)-4 | | 3a-15=24 | | -4(a+4)+8a=-2(2+4a) | | 2=9-5w | | 1-7n-3=-2 | | 5x+y=-23 |